Mycotic aneurysm of superior mesenteric artery caused by Candida albicans in a patient with chronic aortic dissection: The utility of in situ right gastroepiploic artery - Naoto Fukunaga, MD, PhD; Tatsuto Wakami, MD; Akio Shimoji, MD; Otohime Mori, MD; Kosuke Yoshizawa, MD; Nobushige Tamura, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Mycotic aneurysm of the superior mesenteric artery is a rare condition in the literature. Here, we present a case of mycotic aneurysm of the superior mesenteric artery induced by Candida albicans, for which we successfully performed an aneurysmectomy and in situ gastroepiploic artery bypass in a 60-year-old patient with chronic aortic dissection. Postoperative three-dimensional computed tomography angiography revealed the patency of the in situ gastroepiploic artery. Pathology verified the presence of Candida albicans in the aneurysmal wall. In situ gastroepiploic artery restored the antegrade blood supply to the superior mesenteric artery. In addition, use of in situ gastroepiploic artery does not need arterial inflow.